Thermodynamic Properties of Engine Exhaust Gas for Different Kind of Fuels - Kayadelen, H. K.; Ust, Y. (SPRINGER, 2014)
Engine performance highly depends on the thermodynamic properties of the working fluid involved in different processes of engine cycles. However, as engines run with broad range of fuels and fuel air/ratios it is usually not possible to reach thermodynamic tables of products of combustion in the exhaust gas content for a specific fuel/air ratio and at a relevant temperature and pressure. This study addresses a MATLAB adaptable code to investigate engine performance according to the specifically defined thermodynamic properties of the exhaust mixture. Specific heat, enthalpy, entropy and isentropic exponent values are calculated precisely according to the chemical equilibrium approach, assuming there are 10 products of combustion in the exhaust gas content. Graphical illustrations are considered to be reference for future engine performance studies which are derived for different fuels and fuel air ratios under various temperatures and pressures.
Keywords: Exhaust gas; Internal combustion engines; Thermodynamic properties; Engine performance; COMBUSTION PRODUCTS; PREDICTION; EMISSIONS; Mathematics; Physics